Transoceanic Musical Lectures with Jean Luc Raharimanana and Alexandre Vieira (Readings, Concerts and other events, 2023)
In May 2023 the Africa Multiple Cluster of Excellence presented a concert and reading with Jean Luc Raharimanana from Madagascar and Alexandre Vieira from Brazil at @kunst-undkulturhausneunein8931. Jean Luc Raharimanana is a writer from Madagascar who combines writing, theatre, music and photography in his works. Through lyrical, sensuous language influenced by oral tradition, the author portrays not only the beauty of nature but poverty and squalor. In his work, legends and old superstitions are juxtaposed with contemporary political events. Alexandre Vieira is Brazilian bass player and singer that melts his playing with his singing and vice versa, creating, improvising or just playing songs. His music is the sound of his hometown Salvador da Bahia navigating through other cultures, from classical to jazz.